Planners’ Perspectives on British Columbia’s Small and Mid-sized Downtowns: Strengths, Weaknesses, Challenges - Graham, Rylan (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2025)
Downtown revitalization remains a key priority for planners working in communities across North America. In small and mid-sized cities, downtown decline and disinvestment has been particularly noticeable, long affected by the patterns of suburbanization, and more recently, by the lingering effects of the Covid-19 pandemic. This study, based on a survey of planners working in British Columbia, evaluates the state of downtowns in British Columbia’s small and mid-sized cities. These findings highlight the strengths of downtowns as broadband availability, civic events and street-oriented retailed, whereas the most pronounced and common weaknesses are the absence of post-secondary institutions, high-density housing and frequent transit. The findings also illustrate that strengths and weaknesses vary across the cases, accounting for variations in city size and regional contexts. Additionally, this study highlights the prospects and impediments of downtown revitalization into the future, with six major impediments.